Unlock! Escape adventures [games] - Demaegd, Cyril; Santamaria, Pierre; Goyat, Vincent; Legruth; Cauët, Thomas; Gesincourt, Florian de (JD Éditions/Space Cowboys, 2019)
A cooperative card game inspired by escape rooms. Escape rooms are the rooms you need to escape from in less than 60 minutes. Unlock! lets you live these experiences at home around a table. -- The Formula: Enter a secret laboratory to recover a mysterious serum that has been developed by a scientist ... -- Squeek & Sausage: Thwart the plans of the despicable Professor Noside in this cartoon-style adventure! -- The Island of Doctor Goorse: Visit the island of an eccentric antique collector billionaire and overcome its traps!